Respon Pertumbuhan Dan Hasil Tanaman Selada (Lactuca sativa L.) Terhadap Pemberian Dosis Pupuk Kandang Sapi Dan Pupuk NPK - Dari, Hesti Wulan; Prajaka, Nanang Wahyu; Ali, Fahri; Putri, Sekar Utami (Journal of Horticulture Production Technology, 2024)
In 2020, lettuce production in Indonesia was only 101,129 tons, falling short of the market need of 300,204 tons. Fertilizer effects lettuce plant growth and production. The aim of this study was to establish the optimal dosage of cow manure and NPK fertilizer for lettuce plant development and productivity. The research was conducted on agricultural land in Rawa Selapan Village from April to June 2024. This study used a Randomized Block Design (RAK) with two components and three replications. The first factor, the dose of cow manure, had three levels: without cow manure (P0), 100 g/plant (P1), and 200 g/plant (P2). The second factor, the dose of NPK fertilizer, also had three levels: without NPK fertilizer (N0), 2 g/plant (N1), and 4 g/plant (N2). The collected data were examined using analysis of variance, and if there was a significant difference, a 5% BNT test was performed. According to the study's findings, fertilizing with cow manure at a dose of 200 g/plant resulted in better growth and results in the parameters of plant height, number of leaves, wet weight of plots, wet weight of samples, and dry weight of lettuce roots compared to treatments without manure and cow manure at a dose of 100 g per plant. The application of a dose of NPK fertilizer 4 g/plant resulted in good growth and results in the parameters of plant height, leaf width, wet weight per plot, and wet weight of lettuce roots when compared to treatments without NPK fertilizer and NPK fertilizer 2g/plant. No interaction was found between the combination of cow manure and NPK fertilizer dosages.